Physicochemical properties of mango kernel fats extracted from different mango varieties cultivated in Sabah, Malaysia - Aanada H. Jahurul; Chan Y. Ru; Ridhwan Norazlina; Mamat Hasmadi; Matanjun Patricia; Jau Shya Lee; Awal Shihabul; Amir H.M. Shariff; Jumardi Roslan; Noorakmar Ab Wahab; Rezaul Karim; Sharifudin Md Shaarani (Wiley Periodicals Inc., 2024)
Abstract